IDENTIFIKASI KANDUNGAN SENYAWA METABOLIT SEKUNDER PADA BATANG DAN DAUN SURAT DIBATA (Macodes petola) MENGGUNAKAN GAS CHROMATOGRAPHY SPECTROMETRY (GCMS) - Sianturi, Parulian; Dalimunthe, Nur Asyiah; Sahfitra, Angga Ade; Aziz, Rizal; Sihotang, Saipul (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2024)
This study, entitled Identification of Secondary Metabolite Compounds in the Stems and Leaves of Surat Dibata (Macodes petola) Using Gas Chromatography Mass Spectrometry (GCMS) aims to determine the compounds and their concentrations of secondary metabolites present in the stems and leaves of Surat Dibata (Macodes petola) using Gas Chromatography Mass Spectrometry (GCMS). The methods used in this study include maceration extraction to identify secondary metabolite compounds and Gas Chromatography Mass Spectrometry (GCMS) to determine the concentrations of these compounds in the stems and leaves of Surat Dibata (Macodes petola). The results of the study showed that the extraction identified secondary metabolite compounds such as steroids in the stems and flavonoids, steroids, and tannins in the leaves. Based on the results from the GCMS analysis, the stems were found to contain 0.63% steroids, while the leaves contained 0.002% flavonoids, 0.002% tannins, and 2.215% steroids.